Función de los micro-relatos en la teatralización del horror: La gran Semíramis de Virués - Françoise Gilbert; Teresa Rodríguez (Les Cahiers de Framespa)
The purpose of this essay is to show the functions of the micro-narratives in Cristóbal de Virués’s tragedy La gran Semíramis. We’ll study, with several more, that the micro-narratives don’t just have a structural function; they also stresses a serie of generic, formal and semanticle markers, that make La gran Semíramis typical of the tragedy.